Preparing a scale for transformational leadership for administrative bodies from the point of view of Iraqi football club coaches - ِِAli, Mohammed; Naseef , Mohsen (Journal of Physical Education, 2025)
The research aimed to build a scale of transformational leadership for administrative bodies from the point of view of coaches of Iraqi sports clubs in football, which affects the performance of human resources, and to identify the reality of transformational leadership among the administrative bodies in Iraqi sports clubs, as the problem revolves around identifying the reality of the study variables and for transformational leadership and proposing solutions that would raise the level of performance in Iraqi sports clubs in football.  The references and studies related to transformational leadership were reviewed, and the review contained topics related to the research, and the researcher used the descriptive approach in the survey method, and the research community included the coaches of the Iraqi Stars League and Elite clubs for the advanced and youth categories for the sports season (2023-2024), which numbered (325) coaches, including (210) coaches for the advanced category, who constituted a percentage of (65%) of the community, including (115) coaches for the youth category, who constituted a percentage of 35%, and 30 coaches were selected in a simple random manner to be an exploratory sample by 9% of The research community and the selection of 100 trainers in a simple random method to be the sample of building the scale and formed a percentage (31%) and (150) trainers were selected as the sample of the head and constituted (46%).The most important conclusions were the existence of a moral link between the transformational leadership and the reality of the members of the administrative bodies from the point of view of the coaches of the clubs participating in the Iraqi Stars League and the Iraqi football elite, and the researchers reached the most important recommendations, which is to focus on the development of mental and psychological capabilities and skills and develop them among members of the administrative bodies as the most important pillars of achieving sports achievements.